Spectral Study on Selective Encapsulation and Complexation of Chloroform by Cryptophane-E-(OEt)6 - Tao, C.; Li, X.; Li, J.; Shi, Y. (Asian Journal of Chemistry, 2015)
Cryptophane-E-(OEt)6 was synthesized and investigated the interaction with chloroform by fluorescence spectroscopy. The results indicate that cryptophane-E-(OEt)6 is able to selectively encapsulate chloroform. The variation of the fluorescence spectra in binary solvents with the increasing chloroform ratio suggests that cryptophane-E-(OEt)6 and chloroform can form a 1:1 complex and the binding constant is estimated to be 235 M-1, which is much smaller than the binding constant of cryptophane-E to chloroform. Without appreciable consequences on the cavity dimensions, the replacement of methoxy group in cryptophane-E by ethoxy substituents restricts the cross section of the host windows. This is mostly due to steric constraint of the larger ethoxy substituent.